Mapping of New Pharmacological Alternatives in the Face of the Emergence of Antibiotic Resistance in COVID-19 Patents Treated for Opportunistic Respiratory Bacterial Pathogens - Santos, Anamaria Mendonça; Santos, Mariana Mendonça; Nascimento Júnior, José Adão Carvalho; Brito, João Rafael Lisboa Rêgo; de Araújo Andrade, Tatianny; Frank, Luiza Abrahão; Serafini, Mairim R. (Recent Advances in Anti-Infective Drug Discovery, 2022)
Background: The increase in bacterial resistance against antibiotics is thought to be another type of pandemic after COVID-19. Emergency treatment based on antibiotics is a major influence in increasing this resistance. Bacteria, such as Klebsiella pneumoniae, are the most affected by the indiscriminate use of antibiotics, since they are resistant to most antibiotics currently available on the market. Objective: This review aimed to evaluate patents of new drugs and formulations, for the treatment of infections caused by Klebsiella pneumoniae. Methods: The present patent review was carried out through a specialized search database Espacenet. The selection was based on the criteria of patents published from 2010 to May 2021, in any language, and containing the keywords in title or abstract. Also, a research was performed on the PubMed database, using the inclusion criteria. Results: Twenty-two patents were selected for the analysis according to the aim of the study. The advance of new patents has been mostly observed in the World Intellectual Property Organization, China, and United States. The results showed that the main approach was the drug association, followed by drug carriers, new isolated products, and vaccines. Conclusion: It has been observed that few studies use new drug alternatives for the treatment, probably due to the higher cost of the development and lack of investments. The effectiveness and safety of these therapies depend on the acceptance, the correct prescription, and rational use of medicines. Therefore, this review can further develop new treatments as alternatives against Klebsiella pneumoniae and pneumonia caused by it.
Keywords: antibiotics